8 steps to better security : a simple cyber resilience guide for business - Crawley, Kim (John Wiley & Sons, Inc., 2021)
"Harden your business against internal and external cybersecurity threats with a single accessible resource. In 8 Steps to Better Security: A Simple Cyber Resilience Guide for Business, cybersecurity researcher and writer Kim Crawley delivers a grounded and practical roadmap to cyber resilience in any organization. Offering you the lessons she learned while working for major tech companies like Sophos, AT&T, BlackBerry Cylance, Tripwire, and Venafi, Crawley condenses the essence of business cybersecurity into eight steps. Written to be accessible to non-technical businesspeople as well as security professionals, and with insights from other security industry leaders, this important book will walk you through how to: foster a strong security culture that extends from the custodial team to the C-suite; build an effective security team, regardless of the size or nature of your business; comply with regulatory requirements, including general data privacy rules and industry-specific legislation; test your cybersecurity, including third-party penetration testing and internal red team specialists. Perfect for CISOs, security leaders, non-technical businesspeople, and managers at any level, 8 Steps to Better Security is also a must-have resource for companies of all sizes, and in all industries." --